G241(P) More under-fives now seen in urgent care centre than A&E- should we shift our focus?. (27th April 2016) - Gritz, A; Sen, A; Hiles, S; Mackenzie, G; Blair, M
Abstract : Background: Increasing numbers of children are attending Accident and Emergency (A&E) departments, many bypassing primary care services. 1 The reasons for this are complex. 2, 3, 4 Urgent Care Centres (UCCs) in hospital A&Es aim to provide a genuine primary care offering to self-referring patients who bypass primary care and present to A&E. 5 Unfortunately, formal integration between providers of urgent and emergency care operating in the same area is often lacking. 6, 7 Aim: To describe the proportions of under 5s presenting to A&E and UCC at our hospital and identify the GP practices with the highest attendance rates so that we might collaborate and improve pathways for the commonest presenting complaints. Method: A retrospective analysis of routine operational data for attendances of patients under 5 years of age presenting to the A&E and UCC of a large metropolitan district general hospital from 1st October 2013 to 30th September 2014. Data was refined to focus on the patients registered at GP surgeries in the local borough who self-referred and were not admitted. Results: Of 23, 496 attendances to A&E and UCC in the under 5s, 12, 608 (54%) were seen in the UCC and 10, 888 (46%) in A&E. There was a larger divide for the local self-referring non-admitted patients, with 4470 (67%) attending UCC and 2183 (33%) A&E. For the 35 GP Surgeries in the local borough, attendance rates (per 1000 population) varied from 133 to 624 (median 422). Nine practices had attendance rates above the 75th percentile and within this group, the four commonest condition categories 8 were 'fever' (25%), 'injury/foreign body/poisoning/overdose' (17%), 'breathing difficulty/cough' (14%) and 'diarrhoea+/-vomiting' (10%). 20% were coded 'other'. 9 Conclusion: This is the first study characterising borough-wide attendances for A&E and UCC at the same hospital in the under 5s. Surprisingly, most children seeking emergency care are seen at the UCC and not A&E, highlighting the often overlooked need for integrating care between the two. A&E attendance rates varied widely across GP practices in the borough; the reasons for this need exploring further. By focussing on the practices with highest attendance rates and using their most common presenting complaints, we wish to co-develop effective primary care-based interventions.